Increasing rates of cesarean section, an upcoming public health problem: an audit of cesarean section in a tertiary care center of North India based on Robson classification - Das, Vinita; Kumar, Namrata; Kumari, Varsha; Agarwal, Anjoo; Pandey, Amita; Agrawal, Smriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Increasing rates of cesarean section during last three decades has become a cause of alarm since and a need for ongoing studies. Objective of present study was to investigate cesarean section rates as per modified Robsons Criteria and to determine area of concern which requires maximum focus to decrease overall caesarean rate Methods: This cross sectional study was conducted over a period of one year (From January 2016 to December 2016) in the Department of Obstetrics and Gynecology at King George’s Medical University, Lucknow. Results: Total number of deliveries for one year was 8526. Out of them, 4275 (50.1%) were vaginal and 4251 (49.9%) were abdominal. Overall maximum caesarean section rate was contributed by group 5 of modified Robsons criteria i.e. previous section, singleton, cephalic, ≥37 weeks (17.7%). Conclusions: Robson 10 group classification provides easy way in collecting information about Cesarean section rate which obtains good insight into certain birth groups. It is important that efforts to reduce the overall CS rate should focus on reducing the primary CS rate (group 1 and 2) and on increasing vaginal birth after CS (group 5). The caesarean rate is commonest in group 5 that is previous section (17.7%).